2007
DOI: 10.1192/pb.bp.106.013995
|View full text |Cite
|
Sign up to set email alerts
|

Delays in mental health services and duration of untreated psychosis

Abstract: AIMS AND METHODTo dissect duration of untreated psychosis (DUP) into three components: help-seeking delay, referral delay and delay in mental health services, all mental health services in a defined geographical region were screened over a period of 1 year. All cases of first-episode psychosis without a primary mood disorder were identified (n=55).RESULTSThe median delay within secondary services was over seven times the delay in the referral pathway. The mean delay in mental health services accounted for 35% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 13 publications
5
51
1
1
Order By: Relevance
“…It was also hypothesised that GPs in the intervention group would prospectively diagnose young people with first-episode psychosis at an earlier stage in the illness and, therefore, in the longer term decrease the duration of untreated psychosis. There was a possibility that, due to detection bias (that is, GPs in the intervention group identifying young people, some of whom had had the diagnosis for some time 15 ), cases in the control group might have a shorter duration of untreated psychosis during this trial. For these reasons, the number of people referred was chosen as a primary outcome, and the duration of untreated psychosis as one of the secondary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It was also hypothesised that GPs in the intervention group would prospectively diagnose young people with first-episode psychosis at an earlier stage in the illness and, therefore, in the longer term decrease the duration of untreated psychosis. There was a possibility that, due to detection bias (that is, GPs in the intervention group identifying young people, some of whom had had the diagnosis for some time 15 ), cases in the control group might have a shorter duration of untreated psychosis during this trial. For these reasons, the number of people referred was chosen as a primary outcome, and the duration of untreated psychosis as one of the secondary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These findings point toward ethnic differences in the sub-phases of DUP, specifically, the help seeking delay from the time of symptom onset to first contact with health services, and the referral delay from first contact to entry into an appropriate treatment program. [39][40][41] Research from the United Kingdom found that contact with mental health services came later for Black-Caribbean patients, but, once contact was made, this group received psychiatric care sooner. Figure 1 The first contact on the pathway to care for people with first-episode psychosis from 3 ethnic groups in Ontario, n = 171…”
mentioning
confidence: 99%
“…The standardised methodology (Brunet et al, 2007) produced results that are easily comparable with other international studies and different sociocultural contexts. Furthermore, the evaluation of pathways to care by means of several sources of information (patients, relatives, medical professionals) guaranteed the reliability of results.…”
Section: Discussionmentioning
confidence: 73%
“…This may be due to the difficulties of appropriately recognizing early psychotic symptoms, which are wrongly attributed to 'normal' adolescent behaviours (Brunet, Birchwood, Lester, & Thornhill, 2007), to the presence of physical illnesses or use of illicit drugs (Green, Young, & Kavanagh, 2005) or to temperamental characteristics . Moreover, these difficulties have been also attributed to a 'stigma' effect, with patients and relatives trying to avoid psychiatric consultations (Gerlinger, Hauser, & De Hert, 2013) or to organizational aspects of mental health services, such as being located in not easily accessible areas and not advertised (Anderson, Fuhrer, & Malla, 2010).…”
Section: Introductionmentioning
confidence: 99%